Evaluation Of The Cellular Immune Response In Patients With Head And Neck Cancer - Godekmerdan, A.; Kaygusuz, I; Sakallioglu, O.; Ilhan, F.; Demir, N. (Premchand Shantidevi Research Foundation, 2007)
Aim: The aim of the present study is to evaluate the cellular immune response in patients with head and neck cancer. Material-Method: Twenty volunteer healthy subjects as controls and 34 patients who have been diagnosed with squamous cell carcinoma at the Department of Ear Nose Throat in Firat University Firat Medical Center from June 2002 to January 2005 were included in the study. The ages of the patients ranged between 27 and 74 years (mean 56.8+/-10.3), and the ages of the controls ranged from 21 to 69 years (mean 53.4+/-12.7). There were squamous cell carcinoma (SCC) of larynx in 30 patients, SCC of hypo pharynx in three patients, and SCC of paranasal sinus in one patient. 18 of these patients were in the early stage, four patients in the advanced stage, and 14 patients in the metastatic stage. Histopathological diagnoses were carried out by biopsies in preoperative term and pathological examination of the specimens in postoperative term. The examination of lymphocyte sub groups was done by flowcytometiric analysis. Results: In the flow cytometry of peripheral blood samples of head and neck cancer patients and controls, while the ratio of CD4+/CD8+ T cell significantly decreased, the ratio of B lymphocyte, NK cell and activated Tc cell increased in patients compared to the controls. When the patients were compared to each other, CD4+ 25(+) cells were in high level in metastatic patients in comparison to patients in early stages. Conclusion: These results indicated that especially cellular immune response was activated in head and neck cancer, but it was not enough to prevent the cancer
Keywords: Immune response; head and neck cancer